Functionalization of Fullerene C60 with Organic Carbonates in the Presence of a Grignard Reagent and Ti(Oi-Pr)4 - Liliya Khuzina; Artur Khuzin (Chemistry Proceedings)
Fullerene C60 is by far the most studied of all allotropic modifications of carbon. Chemical modification of the double bond over the years has led to the emergence of a variety of fullerene derivatives. These derivatives have now found numerous applications in medicine, materials and supramolecular chemistry, and as efficient electron acceptors in organic photovoltaic devices. The main method for the functionalization of C60 fullerenes, which makes it possible to obtain its derivatives in a preparative volume, is the Bingel–Hirsch reaction. But this method makes it possible to obtain fullerocyclopropanes containing only carboxyl substituents at the bridging carbon atom. Therefore, in order to obtain new materials, we began to study the interaction with organic carbonates in combination with Grignard reagents in the presence of Ti-containing complex catalysts. We hope that replacing the olefin in the Kulinkovich reaction with a C60 fullerene molecule will lead to new and hard-to-find functionalization products of the latter. Organic carbonates were chosen as the object of study due to the fact that they are used in the industry as solvents for natural and synthetic resins, cellulose ethers, dispersants, blowing agents, emulsifiers, absorbents of hydrogen sulfide and carbon dioxide, starting materials for the industrial synthesis of fibers and plastics, as well as plasticizers, pharmaceuticals and plant protection products.